Physiotherapy intervention in Parkinson's disease: systematic review and meta-analysis. (6th August 2012) - Tomlinson, Claire L; Patel, Smitaa; Meek, Charmaine; Herd, Clare P; Clarke, Carl E; Stowe, Rebecca; Shah, Laila; Sackley, Catherine; Deane, Katherine H O; Wheatley, Keith; Ives, Natalie
Abstract : Objective To assess the effectiveness of physiotherapy compared with no intervention in patients with Parkinson's disease. Design Systematic review and meta-analysis of randomised controlled trials. Data sources Literature databases, trial registries, journals, abstract books, and conference proceedings, and reference lists, searched up to the end of January 2012. Review methods Randomised controlled trials comparing physiotherapy with no intervention in patients with Parkinson's disease were eligible. Two authors independently abstracted data from each trial. Standard meta-analysis methods were used to assess the effectiveness of physiotherapy compared with no intervention. Tests for heterogeneity were used to assess for differences in treatment effect across different physiotherapy interventions used. Outcome measures were gait, functional mobility and balance, falls, clinician rated impairment and disability measures, patient rated quality of life, adverse events, compliance, and economic analysis outcomes. Results 39 trials of 1827 participants met the inclusion criteria, of which 29 trials provided data for the meta-analyses. Significant benefit from physiotherapy was reported for nine of 18 outcomes assessed. Outcomes which may be clinically significant were speed (0.04 m/s, 95% confidence interval 0.02 to 0.06, P<0.001), Berg balance scale (3.71 points, 2.30 to 5.11, P<0.001), and scores on the unified Parkinson's disease rating scale (total score −6.15 points, −8.57 to −3.73, P<0.001; activities of daily living subscore −1.36, −2.41 to −0.30, P=0.01; motor subscore −5.01, −6.30 to −3.72, P<0.001). Indirect comparisons of the different physiotherapy interventions found no evidence that the treatment effect differed across the interventions for any outcomes assessed, apart from motor subscores on the unified Parkinson's disease rating scale (in which one trial was found to be the cause of the heterogeneity). Conclusions Physiotherapy has short term benefits in Parkinson's disease. A wide range of physiotherapy techniques are currently used to treat Parkinson's disease, with little difference in treatment effects. Large, well designed, randomised controlled trials with improved methodology and reporting are needed to assess the efficacy and cost effectiveness of physiotherapy for treating Parkinson's disease in the longer term.